The Effect of Motivation and Organizational Climate on Employee Performance (Study at Hikun Office, Tanjung District, Tabalong Regency, South Kalimantan) - Rahmanudin Rahmanudin; Sulastini Sulastini; Maskur Maskur (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Employees currently have many problems related to employment, especially employee performance, therefore problems related to performance need to find a solution. Employees have a very important role and they are the prime mover for smooth performance. Therefore, attention to human resources which is one of the factors for achieving organizational goals is appropriate at the Tabalong District Hikun Office. Focus on two issues, namely (1) Is there an influence of motivation on employee performance at the Tabalong Regency Hikun Office, and (2) Is there an influence of organizational climate on employee performance at the Tabalong Regency Hikun Office. This research method uses a quantitative approach. The number of samples taken was 48 respondents with saturated sampling technique. The data collection technique used a questionnaire (questionnaire), while the data analysis used Smart PLS. The results showed that there was no significant effect of motivation on employee performance at the Tabalong Regency Hikun Office and there was a significant influence of Organizational Climate on employee performance at the Tabalong District Hikun Office. Keywords: Motivation, Organizational Climate, Employee Performance